Methods Used for Reconstruction in Aggressive Bone Tumours: An Early Experience - Pan, K.L.; Sting, S.; Mohamad, A.W.K; GLee, W.; Wong, C.C; Ahmad Hata, Rasit (Malaysian Medical Association, 2003)
Improvements in the overall treatment of patients with aggressive, large tumours involving the bone have made it possible to preserve and salvage limbs instead of amputating them. Each patient is unique in his clinical presentation and social circumstance. The different reconstructive options available allow us to choose the most appropriate method suited to the particular patient and with minimal delay, even when resources are limited. The patient and the relatives actively participate in the choice. The early experience of the different techniques for reconstructing these bone defects at our hospital are presented in this paper.